EXPLORING LEARNERS’ VIEWS ON VOCABULARY LEARNING THROUGH MOVIE CLIPS SUBTITLES IN ESL CLASSES - Taimoor Gurmani; Sehrish Khan; Choudhry Shahid (International Journal of Contemporary Issues in Social Sciences, 2024)
This research explores how individual learning preferences, prior experiences, and engagement levels affect students’ views on this innovative approach compared to traditional vocabulary learning methods. This study investigates the motivations, perspectives, and experiences of participants enrolled in the BS English Programme at a private university in Pakistan regarding using videos with English subtitles for L2 vocabulary learning. The research methodology employed a qualitative design, utilizing semi-structured interviews to gather in-depth insights into participants’ motivations, perspectives, and experiences. Results of the study reveal that the participants’ motivations to use Movie clips with English subtitles are strongly influenced by their individual learning preferences, particularly their preference for visual and experiential learning. They perceive traditional vocabulary learning methods as less engaging and less connected to practical language use. Experiences of those who prefer Movie clips include more active engagement and improved vocabulary retention, while traditional methods are perceived as monotonous and less effective. The implications of this study underscore the significance of accommodating individual learning preferences and prior experiences in language education. Future recommendations include the exploration of diverse student populations and the development of tailored language learning resources that integrate multimedia effectively.